Transgenic Cry1Ab Rice Does Not Impact Ecological Fitness and Predation of a Generalist Spider - Tian, Jun-Ce; Chen, Yang; Li, Zhao-Liang; Li, Kai; Chen, Mao; Peng, Yu-Fa; Hu, Cui; Shelton, Anthony M.; Ye, Gong-Yin (PloS one, 2012)
The commercial release of rice genetically engineered to express a Cry1Ab protein from Bacillus thuringiensis (Bt) for control of Lepidoptera in China is a subject of debate. One major point of the debate has focused on the ecological safety of Bt rice on nontarget organisms, especially predators and parasitoids that help control populations of insect pests. A tritrophic bioassay was conducted to evaluate the potential impact of Cry1Ab-expressing rice on fitness parameters of a predaceous ground spider (Pardosa pseudoannulata (Bösenberg et Strand)) that had fed on Bt rice-fed brown planthopper (Nilaparvata lugens (Stål)) nymphs. Survival, development time and fecundity of this spider were not different when they were fed with Bt rice-fed or non-Bt rice-fed prey. Furthermore, ELISA and PCR gut assays, as well as a functional response trial, indicated that predation by P. pseudoannulata was not significantly different in Bt rice or non-Bt rice fields. The transgenic Cry1Ab rice lines tested in this study had no adverse effects on the survival, developmental time and fecundity of P. pseudoannulata in the laboratory or on predation under field conditions. This suggests that this important predator would not be harmed if transgenic Cry1Ab rice were commercialized.